Invasive lobular carcinoma co-existing with benign phylloides tumor - Shrestha, S; Sigdel, B; Pande, K; Gurung, B (Journal of Pathology of Nepal, 2014)
Phylloides tumor constitutes less than 1% of all breast tumors and 2 - 3% of fibroepithelial breast tumors. Several histological parameters should be evaluated, including stromal cellularity, atypia, mitoses, stromal overgrowth, infiltrative borders, and presence or absence of necrosis. Here we report a case of a 60 years- old female who presented with left breast lump. Fine needle aspiration cytology was done which suggested epithelial hyperplasia with fibrocystic changes. Biopsy was performed which showed predominance of stromal hypercellularity with proliferation of spindle cells (no atypia, mitosis and stromal overgrowth were noticed). However, a focus showed proliferation of discohesive tumor cells arranged singly and in single file. A diagnosis of benign phylloides tumor with foci of invasive lobular carcinoma was made. The diagnosis was confirmed with IHC which showed intense 80%positivity for estrogen and progesterone receptor and spindle cells showing positivity for bcl-2. In situ lobular carcinoma component was not observed. DOI: http://dx.doi.org/10.3126/jpn.v4i7.10321 Journal of Pathology of Nepal (2014) Vol. 4, 597-599